Trends and Fertility Control in South Sumatera Province (Further Analysis of IDHS 2017) - Damayati, Nina; Heldayani, Eni; Anggraini, Winda (Sumatra Journal of Disaster, Geography and Geography Education, 2020)
ABSTRACT: Fertility is a demographic term that concerns the number of babies born alive. Fertility will continue to occur, but the findings of the 2017 IDHS fertility rate per woman (total fertility rate / TFR) in South Sumatra have decreased even though they have not reached the strategic plan targets. The general objective of this research is to find out the fertility picture in South Sumatra Province. The specific purpose of this study is to first analyze fertility trends in 1991-2017. Second, describe the achievement of fertility control. This research approach is quantitative descriptive by utilizing secondary data from the findings of the Demographic and Health Survey of Indonesia (IDHS) South Sumatra Province in 1991-2017. Treat fertility / TFR data to find out trends by analyzing three ways, namely linear trend models, quadratic trends, and exponential trends, whose calculations are assisted with Minitab software version 16. Whereas to find out the achievement of family planning control is to analyze the percentage of the use of modern and traditional family planning tools. The population and sample in this study refer to the 1991-2017 IDHS survey data with the main variables observed being the TFR rate and the use of Modern and Traditional Family Planning devices.The results of the research obtained for fertility trends in South Sumatra in three ways, namely linear trend models, quadratic trends, and exponential trends are showing trends in downtrend patterns with shins in certain ranges, there are extrem uptrens that form bell images, which means that at one time fertility experiences stagnant condition (unchanged), but then fertility has decreased after that. Birth control in South Sumatra is quite good, this can be seen by the adoption of modern family planning devices by 61% and traditional tools / methods by 6%, meaning that 77% of birth control is controlled. It is expected that the family participation rate will continue to increase and the TFR number will fall and be able to meet the national TFR target of 2.3 for the coming years. Keywords: Trends, Control, Fertility, IDHS